Application of the Neuroform Atlas Stent in Intracranial Aneurysms: Current Status - Hou, Kun; Yu, Jinlu (Frontiers in Neurology, 2022)
The Neuroform atlas stent (NAS) is the successor of the Neuroform EZ stent. The NAS is compatible with a low-profile 0.0165-inch microcatheter and is soft enough to pass through highly tortuous and small vessels. The NAS can be used in treating intracranial aneurysms at almost all locations. Currently, use of the NAS is becoming increasingly popular. However, there has not yet been a complete review of NAS applications. Therefore, we performed this review, which covers several aspects, including characteristics of the NAS, clinical trials of the NAS in treating aneurysms, techniques of NAS deployment, rescue stenting with the NAS, application of the NAS for treating distal aneurysms, complications of NAS application, and antiplatelet requirements of NAS application. Through this review, we found that the NAS is promising for the endovascular treatment of intracranial aneurysms, the NAS is appropriate for use in treating complex aneurysms, and the NAS can be used as a routine tool to assist in coiling aneurysms, rescuing coil migration, completing dual stent reconstruction, and covering the aneurysm neck via a transcirculation approach, among other applications. NAS deployment to assist in coiling aneurysms can yield good clinical outcomes and an acceptable rate of complications; thus, the NAS is a promising stent.